Semantic AI in knowledge graphs - Tiwari, Sanju 1979-; Ortiz-Rodriguez, Fernando 1974-; Ben Abbès, Sarra 1985-; Usip, Patience Usoro; Hantach, Rim (CRC Press, 2024)
"Recent combinations of Semantic Technology and Artificial Intelligence presents new techniques to build intelligent systems that identify more precise results. Semantic AI in Knowledge Graphs locates itself at the forefront of this novel development, uncovering the role of machine learning to extend the knowledge graphs by graph mapping or corpus-based ontology learning. Securing efficient results via the combination of symbolic AI and statistical AI such as entity extraction based on machine learning, text mining methods, semantic knowledge graphs, and related reasoning power, this book is the first of its kind to explore Semantic AI and Knowledge Graphs. A range of topics are covered, from: neuro-symbolic AI, explainable AI and deep learning to knowledge discovery and mining, and knowledge representation and reasoning. A trailblazing exploration of semantic AI in knowledge graphs, this book is a significant contribution to both researchers in the field of AI and data mining as well as beginner academicians"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on November 07, 2023)
Keywords: Information visualization -- Congresses; Semantic computing -- Congresses; Artificial intelligence -- Congresses; Visualisation de l'information; Congrès; Informatique sémantique; Congrès; Intelligence artificielle; Congrès; COMPUTERS / Artificial Intelligence; COMPUTERS / Data Modeling & Design; COMPUTERS / Computer Science; Artificial intelligence; Information visualization; Semantic computing; Conference papers and proceedings